The effect of working capital management and policies on manufacturing firm's value based on economic value added - Al-Mawsheki, Randa Mohammed Shams Addin (2020)
This study aimed to analyze the effect of working capital management and working capital policies on economic value added as a measurement for Malaysian manufacturing firm's performance. In this study, working capital management was measured by the cash conversion cycle, inventory conversion cycle, receivable collection period, and account payable period. Meanwhile, working capital policies were measured by the working capital investment policy and working capital financing policy. Working capital financing policy was categorized by aggressive working capital financing policy, conservative working capital financing policy, and matching working capital financing policy. Three main theories were used in the study: capital structure theory, trade-off theory, and pecking order theory. The data included 103 firms with a total of 927 firm-year observations for the period from 2010 to 2018. The study was conducted using panel data and the results showed a significantly negative effect of cash conversion cycle and inventory conversion period on economic value added. However, working capital investment policy, receivable collection period, and account payable period were not significantly related to economic value added. Meanwhile, the aggressive working capital financing policy was positively and significantly related to economic value added. The results suggest that Malaysian manufacturing firms can increase their economic value added by decreasing their cash conversion cycle through decreasing inventory conversion period, which is supported by the pecking order theory. The results also suggest that Malaysian manufacturing firms can increase their economic value added by implementing an aggressive working capital financing policy rather than a matching or a conservative working capital financing policy, which is supported by the trade-off theory.